(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This paper examines the influence of an oxygen environment on the degradation of the operational parameters of strain-sensitive thin films of lead telluride (PbTe). It is shown that the interaction of oxygen with the surface and volume of the films significantly alters their electronic properties, especially at temperatures typical for the operation of thermoelectric and infrared devices. It has been established that the oxygen adsorption process begins on the surface, after which oxygen diffuses along grain boundaries and forms deep acceptor levels in the forbidden band of PbTe, leading to changes in the concentration and mobility of charge carriers.